Sortir du nihilisme : Nietzsche, Mill et l’individualité comme clé de transformation morale et civilisationnelle - Dejardin, Camille (Labyrinth, 2024)
Nietzsche’s criticism of the masses could have looked hackneyed at the end of the XIXth century, had it not the originality of moving onto psychological and biological levels what others previously elaborated only at a social scale: a "herd instinct" explaining both the lack of social cohesion and the loss of possible individual affirmation in democratic and egalitarian ages. As he sees the utilitarian promotion of happiness and empathy as part of the problem, he fiercely condemns John Stewart Mill’s philosophy – as he understands it. Our point is to throw into relief that Mill’s theory of individuality is but closer to Nietzsche’s views for regenerating life against the spreading of democratic "nihilism". Our cross-reading of Mill and Nietzsche therefore aims at offering a reassessment of their antagonism and at highlighting ways of overcoming "nihilism" via culture and cultivation of the "character" and the individual surpassing of oneself.